Antiteuchus tripterus (Fabricius, 1787) (Heteroptera: Pentatomidae): First Record of This Native Stink Bug Damaging the Threatened Araucaria angustifolia in Brazil - Barbosa, Maycon C.; Francisco, Bruno S.; Grazia, Jocélia; Fernandes, José A. M.; Wilcken, Carlos F. [UNESP]; Zanuncio, José C.; Ferreira-Filho, Pedro J. (Springer Nature, 2024)
This is the first report of Antiteuchus tripterus (Fabricius, 1787) (Heteroptera: Pentatomidae) damaging Araucaria angustifolia (Bertol.) Kuntze, 1898 (Pinales: Araucariaceae) plants in Brazil. This bug, native to the neotropical region, damaged this plant on fragments of mixed rain forest in Bueno Brandão, Minas Gerais state, Brazil. Araucaria angustifolia, native and with ecological and economic values, was widely used in the lumber market and, therefore, threatened with extinction. Nymphs and adults of A. tripterus were observed in March and April with a population reduction until June 2022. The bioecology and damage caused by A. tripterus on A. angustifolia are not known.
Keywords: Brazilian pine tree; Forest pest; Integrated management; Monitoring; Plant protection